PROBLEMATIKA PEMBELAJARAN KITAB TAFSIR DI PONDOK PESANTREN PROVINSI RIAU - Jani Arni; Ali Akbar; Hidayatullah Ismail (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article examines the problematic of learning the Tafsir book at Islamic boarding schools. There were 11 Islamic boarding schools in Riau Province that were chosen to be examined, they included: Al-Munawwarah Islamic Boarding School Pekanbaru, Al-Kausar Islamic Boarding School Pekanbaru, Dar El-Hikmah Islamic Boarding School Pekanbaru, Al-Muslimun Islamic Boarding School Pangkalan Kerinci, Hidayatul Ma’rifah Islamic Boarding School Pelalawan, Daarun Nahdhah Islamic Boarding School Bangkinang, Anshar As-Sunnah Islamic Boarding School, Ad-Dar Al-Salafiyah Al-Islamiyah Islamic Boarding School, Sabil Al-Salam Islamic Boarding School, Al-Badr Islamic Boarding School, and Al-Taufik Islamic Boarding School Kampar. Problems such as the appearance of unsatisfying results from the alumni of certain Islamic boarding schools regarding to their knowledge about the Tafsir Book is the reason that this subject is interesting to be examined. The data obtained for this study were collected through interviews with related parties, observation and documentation. Subsequently, the data were presented in accordance to the existed information within the field and followed by analyzing them which corresponded with the proposed main problems. After being examined, there are factors found as the obstacles in learning the Tafsir Book. These factors include the limited teachers which are not equal to the number of students, teachers or ustadh of Tafsir that are not based or graduate from the science of Tafsir, lack of references and others.